After independence : making and protecting the nation in postcolonial & postcommunist states - Barrington, Lowell W., 1968- (Ann Arbor : The University of Michigan Press, 2006)
The majority of the existing work on nationalism has centered on its role in the creation of new states. After Independence breaks new ground by examining the changes to nationalism after independence in seven new states. This innovative volume challenges scholars and specialists to rethink conventional views of ethnic and civic nationalism and the division between primordial and constructivist understandings of national identity. "Where do nationalists go once they get what they want? We know rather little about how nationalist movements transform themselves into the governments of new states, or how they can become opponents of new regimes that, in their view, have not taken the self-determination drive far enough. This stellar collection contributes not only to comparative theorizing on nationalist movements, but also deepens our understanding of the contentious politics of nationalism's ultimate product--new countries."--Charles King, Chair of the Faculty and Ion Ratiu Associate Professor, Georgetown University School of Foreign Service "This well-integrated volume analyzes two important variants of nationalism-postcolonial and postcommunist-in a sober, lucid way and will benefit students and scholars alike."--Zvi Gitelman, University of Michigan Lowell W. Barrington is Associate Professor of Political Science, Marquette University
Nationalism and independence / Lowell W. Barrington -- Nationalism in postcolonial states / Joshua B. Forrest -- From Malay nationalism to a Malaysian nation? / Diane K. Mauzy -- Rwanda: tragic land of dual nationalisms / John F. Clark -- From irredentism to secession: the decline of pan-Somali nationalism / Peter J. Schraeder -- The post-Soviet nations after independence / Ian Bremmer -- Nationalism in post-Soviet Lithuania: new approaches for the nation of "innocent sufferers" / Terry D. Clark -- Kravchuk to the Orange Revolution: the victory of civic nationalism in post-Soviet Ukraine / Taras Kuzio -- Post-Soviet Armenia: nationalism and its (dis)contents / Razmik Panossian -- Georgia: nationalism from under the rubble / Stephen Jones -- Nationalism, nation making, and the postcolonial states of Asia, Africa, and Eurasia / Ronald Grigor Suny.
Includes bibliographical references and index.
Print version record.
English.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Nationalism -- Case studies; Newly independent states -- Politics and government; Postcolonialism -- Case studies; Post-communism -- Case studies; Nationalisme -- Études de cas; Nouveaux États indépendants -- Politique et gouvernement; Postcolonialisme -- Études de cas; Postcommunisme -- Études de cas; POLITICAL SCIENCE -- Political Ideologies -- Nationalism; POLITICAL SCIENCE -- Political Ideologies -- Nationalism & Patriotism; Nationalism; Newly independent states -- Politics and government; Post-communism; Postcolonialism; Nationalisme; Politieke onafhankelijkheid; Postkolonialisme; Postcommunisme; Case studies; Case studies; Études de cas